The Concept of Teachers and Learners in Al-Ghazali's Perspective and its Implications for Education in Indonesia - Septian Kurniasari; Efi Tri Astuti (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2022)
This study aims to determine the concept of educators and students from Al-Ghazali's perspective and its implications for education in Indonesia. To achieve this goal, researchers used the study literature method by examining data sources from books, scientific journals, and research reports, which were then used to identify the concepts of educators and students. The results of this study indicate that the concept of educators according to Al-Ghazali not only provides knowledge but also provides moral development and aligns students' behavior with Islamic religious teachings. Meanwhile, according to Al-Ghazali, the concept of students is that they are natural human beings who need guidance to meet their needs. This article also contributes thoughts on the concept of ideal educators and learners.